Las familias piuranas y su capacidad de comercialización en la segunda mitad del siglo XVIII - Hernández García, Elizabeth (Mercurio Peruano, 2013)
The aim of this paper is to show an initial overview of the economic projection of some great traders piuranos, inserting them in two areas of analysis: family power and political situation of the mideighteenth century.
Keywords: Partido of Piura, Viceroyalty of Peru, Bourbon reforms, regional trade, port of Paita, elites, family power.